(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
This article discusses several internal and external factors that led to the establishment of Taliban power in Afghanistan. The answer to how the Taliban, who tried to seize power several times over the years and failed, can be found while reading the article. Most of the listed internal factors can be seen in how much the Taliban managed to seize power and the consequences of the unstable situation caused by external influences.